(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Parasitic nematodes are one of the main pests causing damage to agricultural crops. Therefore, the study of their structure, bioecology and distribution characteristics is considered a necessary factor that helps to increase productivity and quality.